The age of god-kings: TimeFrame 3000 - 1500 BC (Alexandria, Virginia, 1987)
This book describes the historical events and the various civilizations that flourished throughout the world, with emphasis on the Sumer area, the world's first civilization, from 1500 to 600 BC.
Keywords: history, ancient